الأنا وتمثيل الآخر في رحلة ابن حمادوش الجزائري - بودربالة, يزيد; بو مهرة, عبد العزيز (جامعة الوادي - University of Eloued, 2021)
ملخص: تهدف هذه الدراسة إلى تناول الأنا وتمثيل الآخر في رحلة عبد الرزاق ابن حمادوش، الذي انتقل من الجزائر إلى المغرب الأقصى في القرن الثاني عشر للهجرة(الثامن عشر ميلادي)، وحرص على تصوير المغربي -وفق رؤيته الخاصة- من جوانب عدة، فامتدح بعضها وانتقد البعض الآخر، واكتفى في المقابل بسرد بعض الأمور المتعلقة بالمغربي دون إطلاق حكم واضح حيالها، من هنا سعينا إلى إبراز الصورة المقدمة لهذا الآخر اجتماعيا ودينيا وسياسيا وعلميا. Abstract: This study aims at dealing with the self and the representation of the other in the journey of Abd Errazak Ibn Hamadouche.The latter moved from Algeria to Morocco in the twelfth century hijri(eiteenth ad)ˌand he insisted on depicting the Moroccan according to his own vision from different sides⁏ he complimented some of them and criticized others.On the other handˌhe just reported some issues related to the Moroccan without making aclear judgement about them.Henceˌwe sought to show the image presented to this ˈotherˈsociallyˌreligiouslyˌpoliticallyˌand scientifically.
مقال
Keywords: الأنا ; الآخر ; رحلة ابن حمادوش ; المغرب الأقصى ; القرن الثاني عشر للهجرة